2021
DOI: 10.1111/ijcs.12687
|View full text |Cite
|
Sign up to set email alerts
|

Theory of consumption values in consumer behaviour research: A review and future research agenda

Abstract: Woodruff, 1997). Marketing is accepted as a value-creation discipline based on current marketing philosophy (Kotler, 2020;Liu, 2017). Thus, marketing is responsible for building, maintaining,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 104 publications
(254 reference statements)
0
62
0
Order By: Relevance
“…'s (2021) review on in‐store mobile device usage, Goyal and Kumar's (2021) review on financial literacy, Kapoor and Banerjee's (2021) review on brand scandal, Mamun et al's (2021) review on Islamic marketing, Mishra et al. 's (2021) review on omnichannel retailing, Rebouças and Soares's (2021) review on voluntary simplicity, Tanrikulu's (2021) review on theory of consumption values, and Wang et al's (2021) review on consumer choice models and reference points.…”
Section: Exemplars Of Systematic Literature Reviewsmentioning
confidence: 99%
“…'s (2021) review on in‐store mobile device usage, Goyal and Kumar's (2021) review on financial literacy, Kapoor and Banerjee's (2021) review on brand scandal, Mamun et al's (2021) review on Islamic marketing, Mishra et al. 's (2021) review on omnichannel retailing, Rebouças and Soares's (2021) review on voluntary simplicity, Tanrikulu's (2021) review on theory of consumption values, and Wang et al's (2021) review on consumer choice models and reference points.…”
Section: Exemplars Of Systematic Literature Reviewsmentioning
confidence: 99%
“…Rapid technological advancements have brought a shift in marketing strategies and consumer behavior (Ameen et al, 2021; Chan & Li, 2010). Companies have quickly moved on using information technological capabilities (ITC) to meet the ever‐changing customer expectations (Djellal & Gallouj, 2001; Gallouj & Savona, 2009; Tanrikulu, 2021). These technological implications have changed the market dynamics from offline to online (Ostrom et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Second, we extend consumption values theory by identifying the multi-dimensional impact of value characteristics on purchase behavior in a context of emerging industrial and social importance. This reflects the further investigation requirements in the research agenda identified in Tanrikulu [68] that suggests there is merit in further understanding the perceived value in the purchase of new product types (e.g., premium content in our research) in the context of the digital world.…”
Section: Discussion Contributions and Limitationsmentioning
confidence: 70%